Utilization of the Hydroelectric Potential of the Pomorskie Voivodship - Krzysztof Kowalczyk; Roman Cieśliński (Barometr Regionalny, 2018)
One of the sources of electricity used by man is water. Currently the idea of hydroelectric power plants is increasingly appreciated by local governments. Sustainable development and EU directives have required the construction of green power plants. The article outlines the energy situation of the Pomorskie Voivodship. As a result, it was found that more than half of the energy consumed in the region is produced outside its area. Considering the transmission losses, this is a disadvantage. Hydropower installations are increasingly appearing in the voivodship, but there are relatively few of them. The natural and anthropogenic conditions of more than 300 potential hydropower plants have been analyzed. Based on the conducted research, the hydroelectric potential of the voivodship was estimated and the best locations for hydropower were identified.